2014
DOI: 10.1007/s40279-014-0160-3
|View full text |Cite
|
Sign up to set email alerts
|

Are Post-Exercise Appetite Sensations and Energy Intake Coupled in Children and Adolescents?

Abstract: The effect of physical activity on energy balance is not restricted to its induced energy expenditure but also affects the control of energy intake and appetite. Although it is now clear that physical exercise affects subsequent energy intake and appetite, the mechanisms involved remain uncertain. Most previous studies have assessed both post-exercise energy intake and appetite but mainly focussed their analyses on food consumption, and it remains unclear whether changes in appetite provide an accurate reflect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 40 publications
9
21
0
Order By: Relevance
“…The lack of a significant difference in appetite sensations between the conditions is in line with previous research that showed that seated video games do not increase hunger sensations (3) and that appetite sensations also do not differ after exercise interventions in adolescents (11). The addition of measures of appetite hormones in the current study would allow for further exploration of these results.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The lack of a significant difference in appetite sensations between the conditions is in line with previous research that showed that seated video games do not increase hunger sensations (3) and that appetite sensations also do not differ after exercise interventions in adolescents (11). The addition of measures of appetite hormones in the current study would allow for further exploration of these results.…”
Section: Discussionsupporting
confidence: 88%
“…According to exercise intervention studies, the time frame for compensation (if it occurs) has not yet been clearly established but can range from hours to over several days (9)(10)(11)15). Participants were instructed on how to complete the dietary record and on how to measure quantities of ingested foods.…”
Section: Dietary Recordmentioning
confidence: 99%
See 1 more Smart Citation
“…This absence of post-exercise modification of the EI derived from each macronutrient remains difficult to interpret due to limited and contradictive results in this population [11,18,27,28]. Our results regarding appetite feelings confirm once more the previously described “uncoupling effect” of acute exercise on appetite sensations and EI [29], since hunger, satiety or prospective food consumption were not modified by exercise in either lean or obese adolescents. This was despite the fact that obese adolescents showed a decrease in EI following EX compared to CON.…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, the reduction in energy intake observed in obese adolescents is not accompanied by any modification of their subjective sensations of motivation to eat (e.g. hunger and satiety) .…”
Section: Introductionmentioning
confidence: 91%